A study of superluminous stars with the Fermi-Large Area Telescope. Issue 1 (26th July 2021) - de Menezes, Raniere; Orlando, Elena; Di Mauro, Mattia; Strong, Andrew
ABSTRACT: The γ-ray emission from stars is induced by the interaction of cosmic rays with stellar atmospheres and photon fields. This emission is expected to come in two components: a stellar disc emission, where γ-rays are mainly produced in atmospheric showers generated by hadronic cosmic rays, and an extended halo emission, where the high density of soft photons in the surroundings of stars create a suitable environment for γ-ray production via inverse Compton (IC) scattering by cosmic ray electrons. Besides the Sun, no other disc or halo from single stars has ever been detected in γ-rays. However, by assuming a cosmic ray spectrum similar to that observed on Earth, the predicted γ-ray emission of superluminous stars, e.g. Betelgeuse and Rigel, could be high enough to be detected by the Fermi Large Area Telescope (LAT) after its first decade of operations. In this work, we use 12 yr of Fermi -LAT observations along with IC models to study nine superluminous nearby stars, both individually and via stacking analysis. Our results show no significant γ-ray emission, but allow us to restrict the stellar γ-ray fluxes to be on average <3.3 × 10 −11 ph cm −2 s −1 at a 3σ confidence level, which translates to an average local density of electrons in the surroundings of our targets to be less than twice of that observed for the Solar system.